2015
DOI: 10.1080/09297049.2015.1023272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of motivation on academic fluency performance in survivors of pediatric medulloblastoma

Abstract: It has been proposed previously that extrinsic motivation may enable survivors of childhood medulloblastoma to significantly improve aspects of neurocognitive performance. In healthy populations, enhanced motivation has been shown to promote academic fluency, a domain likely more relevant to the educational outcomes of pediatric medulloblastoma survivors than academic skill development. The present study investigates the effect of enhanced extrinsic motivation on fluent (i.e., accurate and efficient) academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
4
0
1
Order By: Relevance
“…Supporting this idea, several studies have demonstrated associations between various types of sleep disruption and lower engagement in tasks that are perceived as more cognitively demanding ( Engle-Friedman et al, 2010 , 2018 ; Libedinsky et al, 2013 ). Further, the impact of motivation on performance in PBT survivors was illustrated by Holland et al (2016) , who demonstrated that external incentive improves effort on discrete timed academic tasks, indicating that motivation is a fluctuating variable that can substantively alter the situational performance of PBT survivors. Considering these findings, it may be that PBT survivors who experience sleep difficulties may choose less effortful activities when possible, and this choice may be available to a lesser extent during a neuropsychological evaluation as compared to daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this idea, several studies have demonstrated associations between various types of sleep disruption and lower engagement in tasks that are perceived as more cognitively demanding ( Engle-Friedman et al, 2010 , 2018 ; Libedinsky et al, 2013 ). Further, the impact of motivation on performance in PBT survivors was illustrated by Holland et al (2016) , who demonstrated that external incentive improves effort on discrete timed academic tasks, indicating that motivation is a fluctuating variable that can substantively alter the situational performance of PBT survivors. Considering these findings, it may be that PBT survivors who experience sleep difficulties may choose less effortful activities when possible, and this choice may be available to a lesser extent during a neuropsychological evaluation as compared to daily life.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, training parents in behavioral modification, cognitive instructional methods and compensatory strategies to allow for ongoing intervention in the child’s natural environment showed some efficacy in improving academic outcomes and warrants further attention [ 111 ]. As another example, a recent randomized study isolated improvements in situational motivation as associated with improved academic performance [ 112 ]. Situational and intrapersonal factors such as level of intrinsic achievement motivation and responsivity to external incentive may have a role in improving academic performance in PBT survivors.…”
Section: Interventions To Support Pbt Survivorsmentioning
confidence: 99%
“…Results suggested modest benefit relative to non-intervention controls on specific academic test scores, and a correlation was noted between time spent in intervention and improvement on a reading comprehension task [ 92 ]. External incentives have shown the potential to improve situational academic performance in PBT survivors [ 93 ], suggesting that intrapersonal factors, such as level of intrinsic achievement motivation and responsivity to situational incentive may be fruitful areas of future research.…”
Section: Educational Pain Management For Pediatric Brain Tumor Survivorsmentioning
confidence: 99%